2023
DOI: 10.3389/fnagi.2023.1201142
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis and prediction of Alzheimer’s disease and alcohol dependence based on Ferroptosis-related genes

Abstract: BackgroundAlzheimer’s disease (AD) is a neurodegenerative disease whose origins have not been universally accepted. Numerous studies have demonstrated the relationship between AD and alcohol dependence; however, few studies have combined the origins of AD, alcohol dependence, and programmed cell death (PCD) to analyze the mechanistic relationship between the development of this pair of diseases. We demonstrated in previous studies the relationship between psychiatric disorders and PCD, and in the same concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 55 publications
(61 reference statements)
0
1
0
Order By: Relevance
“… 14 , 15 Furthermore, miRNAs such as miR‐132, miR‐34a, miR‐124, and miR‐106b have been linked to AD and are believed to play important roles in various aspects of the disease, including neuroinflammation, synaptic dysfunction, and neurodegeneration. 16 , 17 , 18 Intriguingly, studies have identified altered miRNA expression patterns in blood that could serve as potential diagnostic markers for AD. Examples of such miRNAs include miR‐134, miR‐193b, and miR‐384, which have been found to be significantly altered in AD patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Furthermore, miRNAs such as miR‐132, miR‐34a, miR‐124, and miR‐106b have been linked to AD and are believed to play important roles in various aspects of the disease, including neuroinflammation, synaptic dysfunction, and neurodegeneration. 16 , 17 , 18 Intriguingly, studies have identified altered miRNA expression patterns in blood that could serve as potential diagnostic markers for AD. Examples of such miRNAs include miR‐134, miR‐193b, and miR‐384, which have been found to be significantly altered in AD patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%